2020
DOI: 10.1111/trf.16204
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of variant alleles encoding Kidd, Duffy, and Kell antigens in individuals with sickle cell disease using whole genome sequencing data from the NHLBI TOPMed Program

Abstract: Background Genetic variants in the SLC14A1, ACKR1, and KEL genes, which encode Kidd, Duffy, and Kell red blood cell antigens, respectively, may result in weakened expression of antigens or a null phenotype. These variants are of particular interest to individuals with sickle cell disease (SCD), who frequently undergo chronic transfusion therapy with antigen‐matched units. The goal was to describe the diversity and the frequency of variants in SLC14A1, ACKR1, and KEL genes among individuals with SCD using whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Another study objective is to optimize RBC unit characteristics that patients with SCD and thalassemia receive (beyond RBC phenotype matching for Rh C, E and K antigens), so as to minimize iron loading and iron toxicity. 40 Thus, aim 2 will measure markers of hemolysis and iron parameters before and two hours after single-unit transfusion in simply transfused patients with SCD (in both the US and Brazil), thalassemia (US only), or in pediatric patients with a hematologic/oncologic diagnosis and a hypo-proliferative bone marrow (US only). Since anemia in these patient populations is due to differing pathophysiology, it is hypothesized that the relationship between blood donor, manufacturing, and recipient factors and change in serum iron after transfusion will differ by disease.…”
Section: Red Blood Cell -Improving Transfusions For Chronically Trans...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study objective is to optimize RBC unit characteristics that patients with SCD and thalassemia receive (beyond RBC phenotype matching for Rh C, E and K antigens), so as to minimize iron loading and iron toxicity. 40 Thus, aim 2 will measure markers of hemolysis and iron parameters before and two hours after single-unit transfusion in simply transfused patients with SCD (in both the US and Brazil), thalassemia (US only), or in pediatric patients with a hematologic/oncologic diagnosis and a hypo-proliferative bone marrow (US only). Since anemia in these patient populations is due to differing pathophysiology, it is hypothesized that the relationship between blood donor, manufacturing, and recipient factors and change in serum iron after transfusion will differ by disease.…”
Section: Red Blood Cell -Improving Transfusions For Chronically Trans...mentioning
confidence: 99%
“…Iron‐related tissue toxicity is a major cause of morbidity and mortality in regularly transfused patients. Another study objective is to optimize RBC unit characteristics that patients with SCD and thalassemia receive (beyond RBC phenotype matching for Rh C, E and K antigens), so as to minimize iron loading and iron toxicity 40 . Thus, aim 2 will measure markers of hemolysis and iron parameters before and two hours after single‐unit transfusion in simply transfused patients with SCD (in both the US and Brazil), thalassemia (US only), or in pediatric patients with a hematologic/oncologic diagnosis and a hypo‐proliferative bone marrow (US only).…”
Section: Transfusion Recipient Outcomesmentioning
confidence: 99%
“…Patients from different population groups experience higher rates of transfusion‐associated non‐infectious adverse events, in part due to genetic differences between donors and recipients in red blood cell groups (Rh), platelet and human leukocyte antigens (HLA) 52,72,73 . Adverse events include alloimmunization, delayed hemolytic transfusion reactions (DHTR), and poor stem cell engraftment which are associated with significant morbidity and mortality 74 .…”
Section: Research Prioritiesmentioning
confidence: 99%
“…Rh variants in SCD patients have been extensively studied, but variant alleles of Kell, Kidd, and Duffy blood group systems are less characterized. Dinardo et al performed WGS on 3274 patients to assess diversity and frequency of variant alleles in these systems 40 . Investigators identified variant alleles conferring null phenotypes or weakened expression, while also identifying several novel alleles.…”
Section: Immunohematology and Genomicsmentioning
confidence: 99%
“…Dinardo et al performed WGS on 3274 patients to assess diversity and frequency of variant alleles in these systems. 40 Investigators identified variant alleles conferring null phenotypes or weakened expression, while also identifying several novel alleles.…”
Section: Variant Allelesmentioning
confidence: 99%